Digital-enabled dynamic capabilities for circular economy: The role of firm size - Alberto Urueña; Alessandra Neri; Enrico Cagno; Ebru Susur (Journal of Cleaner Production, 2026)

Individual alpha frequency tACS modifies the detection of space–time optical illusion - Francesco Neri; Vincenzo Catrambone; Alessandra Cinti; Adriano Scoccia; Alberto Benelli; Sara Romanella; Laetitia Grabot; Gaetano Valenza; Carmelo Luca Smeralda; Emiliano Santarnecchi; Virginie van Wassenhove; Simone Rossi (Experimental Brain Research, 2025)
Postdiction is a perceptual phenomenon where the perception of an earlier stimulus is influenced by a later one. This effect is commonly studied using the ‘rabbit illusion’, in which temporally regular, but spatially irregular, stimuli are perceived as equidistant. While previous research has focused on short inter-stimulus intervals (100–200 ms), the role of longer intervals, which may engage late attentional processes, remains unexplored. This study investigates whether postdiction is purely perceptual or also involves attentional mechanisms by using visual stimuli separated by extended intervals. 33 participants (17 females) were assigned to two experimental groups with two different temporal inter-flash intervals (IFI) between stimuli (250 ms: 250-IFI group; 500 ms: 500-IFI). Two stimulation protocols of active transcranial electrical stimulation (tES) and one control condition were tested on the left precuneus/inferior parietal gyrus: (i) transcranial alternating current stimulation (tACS) at the individual alpha frequency (IAF) (IAF-tACS); (ii) transcranial random noise stimulation across the whole alpha band (i.e., 8–12 Hz, Alpha-tRNS) and (iii) a placebo (Sham) stimulation. The postdiction phenomenon was observable in both experimental groups. The participants in the 500-IFI group demonstrated enhanced performance in detecting the illusion during the rabbit illusion task when IAF-tACS was applied. The behavioral results suggest that attentional functions, beyond perceptual ones, play a key role in the postdiction phenomenon.

Understanding how circular economy practices and digital technologies are adopted and interrelated: A broad empirical study in the manufacturing sector - Enrico Cagno; Sandra Naomi Morioka; Alessandra Neri; Erivaldo Lopes de Souza (Resources, Conservation and Recycling, 2025)

Barriers and drivers to the development of an effective water reuse chain: insights from an Italian water utility - Alessandra Neri; Andrea Rizzuni; Paola Garrone; Enrico Cagno (Clean Technologies and Environmental Policy, 2025)
Widespread adoption of water reuse technologies is critical to the development of a circular economy and to reduce the pressure on increasingly scarce freshwater resources. However, the adoption of water reuse technologies involves a complex and multi-level decision-making process, influenced by different factors that hinder or support such adoption, namely barriers and drivers. The present research provides a first identification of such factors from a value chain perspective. To do so, the paper first conceptualises the water reuse value chain, including the actors and stages required to bring collected wastewater to the reuse destination. It then conducts an exploratory case study in the context of an Italian water utility facing increasing water stress. External barriers such as societal perceptions and lack of demand for recycled water emerge as particularly influential in hindering the adoption of water reuse technologies. Drivers emerge from both the external and internal environment, with the level of water scarcity and the effectiveness of collaboration and coordination between different institutional and policy actors being particularly strong. Barriers and drivers are found to be of varying relevance depending on the characteristics of the facilities and the reuse value chain analysed, including the operational status of the reclamation facility, the type of final reuse, and the roles in the value chains. The paper provides relevant implications for academics, policymakers, and adopters of water reuse technologies for a more circular and environmentally sustainable water sector, offering useful insights for decision-makers in related sectors. Graphical abstract

Short-term machinery impact on microbial activity and diversity in a compacted forest soil - Agnese Bellabarba; Laura Giagnoni; Alessandra Adessi; Elena Marra; Andrea Laschi; Francesco Neri; Giovanni Mastrolonardo (Applied Soil Ecology, 2024)

Seasonal variability of epipelic microphytobenthos community in two subtidal areas of the Northern Adriatic Sea - APURVA MULE; FRANCESCA NERI; TIZIANA ROMAGNOLI; STEFANO ACCORONI; FRANCESCA CARIDI; ALESSANDRA CAMPANELLI; MARIKA UBALDI; DIANA SARNO; CECILIA TOTTI (Mediterranean Marine Science, 2024)
We investigated the biodiversity and seasonality of subtidal benthic diatoms at two sites of the Northern Adriatic Sea differently affected by anthropogenic inputs. Sediment samples were collected seasonally, and diatom cells were then separated from the sediment using the density gradient centrifugation method. The total abundance of benthic diatoms ranged between 4,409 ± 1,638 and 77,663 ± 30,415 cells cm-2 and the biomass between 0.41 ± 0.22 and 3.66 ± 2.01 μg C cm-2. At both stations, the benthic diatoms showed a marked seasonal pattern, with maximum abundance, biomass and biodiversity in spring and minimum in summer. Motile life forms, such as Navicula, Nitzschia, Fallacia, and Psammodictyon, dominated in terms of abundance at both stations throughout the study period, while plocon (centric diatoms mainly belonging to Biddulphiaceae) increased under mixing conditions, when they represented the largest contributor to biomass. At both stations and in all seasons, the Si:N:P ratio highlighted the strong P limitation, typical of the Adriatic Sea. The ammonium concentration was the highest component of DIN in spring and summer when we observed the highest and lowest MPB abundance respectively. The preference of diatoms for ammonia, coupled with the increased daylight period, may have enhanced the spring growth, whereas in summer the hypoxic conditions may have caused a decrease. Despite the different environmental conditions, the two stations exhibited similar species compositions and seasonal trends, highlighting relative stability against anthropogenic pressures of a different nature.

Influence of policymakers and civil society stakeholders on sewage sludge management strategies: Empirical results from European utilities - Alessandra Neri; Andrea Rizzuni; Paola Garrone; Enrico Cagno (Journal of Environmental Management, 2024)

Detection of morphological and eco-physiological traits of ornamental woody species to assess their potential Net O3 uptake - Jacopo Manzini; Yasutomo Hoshika; Pierre Sicard; Alessandra De Marco; Francesco Ferrini; Emanuele Pallozzi; Luisa Neri; Rita Baraldi; Elena Paoletti; Barbara Baesso Moura (Environmental Research, 2024)

Investigating the entrepreneurial orientation of circular-social hybrid start-ups by assessing their path toward sustainability: Evidence from 20 European cases - Charleen von Kolpinski; Enrico Cagno; Alessandra Neri (Sustainable Production and Consumption, 2024)

Flavonoid- and limonoid-rich extracts from lemon pomace by-products: Technological properties for the formulation of o/w emulsions - Francesco Iervese; Federica Flamminii; Giulia D'Alessio; Lilia Neri; Alessandra De Bruno; Valeria Imeneo; Luca Valbonetti; Carla Daniela Di Mattia (Food Bioscience, 2024)

Could persistent organic pollutants affect future generations of sea turtles by maternal transfer? First results for Caretta caretta nests along the North-Western coast of Italy - Ilaria Ceciarini; Francesca Capanni; Lorenzo Minoia; Guia Consales; Carlo Amico; Marco Alberto Luca Zuffi; Giuliana Terracciano; Cecilia Mancusi; Alessandra Neri; Enrica Franchi; Giovanni Raimondi; Alessia Prestanti; et al. (Frontiers in Marine Science, 2024)
Since 2013, loggerhead sea turtle ( Caretta caretta , Linnaeus 1758) nesting has been observed further north along the Italian coast, reaching the Tuscan coast (NW Mediterranean Sea). The four nesting events that occurred in Tuscany in the summer of 2019 spurred the scientific community to monitor these occurrences more carefully, following them from egg deposition to hatching. This provided an opportunity to collect samples for conducting multidisciplinary investigations, including the toxicological investigations of the biological material collected from the four nests. The aim of this study was to conduct an initial assessment of persistent organic pollutants in the eggs laid in Tuscany, aiming to establish a baseline on this topic for subsequent nesting events that have occurred until today. Organochlorine compounds (OCs), specifically polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DDT) and its metabolites, and hexachlorobenzene (HCB), were analyzed and detected in unhatched eggs, embryos, and chorio-allantoic membranes (CAMs). OCs were detected in all samples, with PCBs > DDTs ≫ HCB. A significant spatial variation in pollutant levels and profiles among sea turtle nesting locations was found. Embryos showed higher levels of contamination than egg contents regardless of the developmental stages. Depth of the laying chamber and egg mass were not significant factors in OC bioaccumulation. For the first time in the Mediterranean Sea, this study assessed the role of CAM in the transfer of contaminants to the embryo. Overall, the OC levels found were lower compared to the results from other studies conducted worldwide on loggerhead sea turtle biological material. This was the first assessment of nest biological material for the North-Western coast of Italy.

Persistent Organic Pollutants (POPs) in three bathyal chondrichthyes from the North-Western Mediterranean Sea - Guia Consales; Massimiliano Bottaro; Cecilia Mancusi; Alessandra Neri; Paolo Sartor; Alessandro Voliani; Antonella D'Agostino; Letizia Marsili (Marine Pollution Bulletin, 2023)

Phytoplankton communities in a coastal and offshore stations of the northern Adriatic Sea approached by network analysis and different statistical descriptors - Francesca Neri; Tiziana Romagnoli; Stefano Accoroni; Marika Ubaldi; Angela Garzia; Andrea Pizzuti; Alessandra Campanelli; Federica Grilli; Mauro Marini; Cecilia Totti (Estuarine, Coastal and Shelf Science, 2023)

Range expansion of the Atlantic fish Zenopsis conchifer (Lowe, 1852), family Zeidae, in the western Mediterranean Sea - CECILIA PINTO; GIOVANNI ROPPO VALENTE; NICOLA RASORE; EDOARDO OLMI; LUCA LANTERI; FULVIO GARIBALDI; CLAUDIO VIVA; ALESSANDRA NERI; ANDREA MASSARO; FRANCESCO De CARLO; ALESSANDRO LIGAS; PAOLO SARTOR (Mediterranean Marine Science, 2023)
Three specimens of Silver John dory, Zenopsis conchifer, (Lowe, 1852) were observed for the first time in the Ligurian Sea and northern Tyrrhenian Sea (western Mediterranean), one in 2020 and two in 2021. This is the fifth record (up to ten individuals) of Z. conchifer in the Mediterranean Sea, which occurred 11 years after the last observation in 2010 in the southern Tyrrhenian Sea. The present study reports the northernmost record of the species in the western Mediterranean Sea, indicating a potential range expansion of the distribution of this Atlantic species across the area. Morphometric, meristic and biological data of the three specimens are provided and compared with previous published records.

Efficiency of consumer behaviour and digital ecosystem in the generation of the plastic waste toward the circular economy - Fahimeh Khatami; Šárka Vilamová; Enrico Cagno; Paola De Bernardi; Alessandra Neri; Valter Cantino (Journal of Environmental Management, 2023)

AFG3L2 Biallelic Mutation: Clinical Heterogeneity in Two Italian Patients - Fabiana Colucci; Marcella Neri; Fernanda Fortunato; Alessandra Ferlini; Rosalba Carrozzo; Alessandra Torraco; Eleonora Lamantea; Andrea Legati; Ginevra Tecilla; Maura Pugliatti; Mariachiara Sensi (The Cerebellum, 2022)

Palytoxin-Analogues Accumulation in Natural Mussel Banks during an Ostreopsis cf. ovata Bloom - Stefano Accoroni; Marika Ubaldi; Simone Bacchiocchi; Francesca Neri; Melania Siracusa; Maria Giovanna Buonomo; Alessandra Campanelli; Cecilia Totti (Journal of Marine Science and Engineering, 2022)
Intense blooms of the toxic dinoflagellate Ostreopsis producing palytoxin (PlTX) analogs, mainly ovatoxins (OVTXs), have been a recurrent phenomenon along several Mediterranean coasts. Although there is evidence of seafood contamination by these toxins, the dynamics of their bioaccumulation during Ostreopsis blooms is not yet clear. Toxin concentrations in wild mussels at two sites in the Conero Riviera, along the northern Adriatic Sea (Portonovo and Passetto), were analyzed from August to October 2021, throughout an Ostreopsis cf. ovata bloom, to investigate their relationships with the bloom pattern and abundances. Contaminated mussels showed the typical toxin profile dominated by OVTX-a and -b, with levels lower than the threshold considered unsafe for human consumption (30 µg PlTX-equivalent kg−1 soft tissue). The toxin content reached 36.4 µg PlTX kg−1 soft tissue only in a single sampling date. A clear correlation between the bioaccumulation of OVTXs in mussels and the abundance of Ostreopsis was observed. Our results highlighted, however, that bioaccumulation in the mussels is not affected merely by the abundance of toxic microalgae, since higher toxin levels were recorded at Portonovo, where the cell abundances were lower than at Passetto. The results from this study indicate that the Italian guidelines for the management of Ostreopsis blooms in bathing waters are also useful in managing the risks of human intoxication through ingestion, as mussel contamination was detected only during the alert phase (10,000–30,000 cells L−1).

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Proline accumulation induces the production of total phenolics in transgenic tobacco plants under water deficit without increasing the G6PDH activity - Fláive Loyze Baldassarini Silva; Luiz Gonzaga Esteves Vieira; Alessandra Ferreira Ribas; Adriana Lima Moro; Daniel Moreira Neris; Ana Cláudia Pacheco (Theoretical and Experimental Plant Physiology, 2018)

Use of Arsenic Contaminated Irrigation Water for Lettuce Cropping: Effects on Soil, Groundwater, and Vegetal - Claudio Beni; Simona Marconi; Priscilla Boccia; Alessandra Ciampa; Giampietro Diana; Rita Aromolo; Elena Sturchio; Ulderico Neri; Paolo Sequi; Massimiliano Valentini (Biological Trace Element Research, 2011)

Biomarkers of Exposure and Effects for Assessing Toxicological Risk of Endocrine Disrupters in Top Predators of the Mediterranean Sea - M. Cristina Fossi; Silvia Casini; Letizia Marsili; Stefania Ancora; Gabriele Mori; Giovanni Neri; Antonella Ausili; Teresa Romeo; Alessandra Moscatelli; Giuseppe Notarbartolo Di Sciara (Marine Ecology, 2002)
Endocrine Disrupting Chemicals (EDCs) have the potential to alter hormone pathways that regulate reproductive processes in wildlife and fisheries. In this research the unexplored hypothesis that Mediterranean top predator species (such as large pelagic fish and marine mammals) are potentially at risk due to EDCs is investigated. In the Mediterranean environment, top predators accumulate high concentrations of polyhalogenated aromatic hydrocarbons (PHAHs) and toxic metals, incurring high toxicological risk. Here we illustrate the need to develop sensitive biomarkers for evaluation of toxicological risk in top marine predators (Xiphias gladius, Thunnus thynnus thynnus) and non‐lethal techniques, such as non‐destructive biomarkers, for the hazard assessment of threatened species exposed to EDCs, such as marine mammals ( Stenella coeruleoalba, Tursiops truncatus, Delphinus delphis and Balaenoptera physalus ).

Mutations of the 'minor' mismatch repair gene MSH6 in typical and atypical hereditary nonpolyposis colorectal cancer - Emanuela Lucci-Cordisco; Valentina Rovella; Stefania Carrara; Antonio Percesepe; Monica Pedroni; Alfonso Bellacosa; Oana Caluseriu; Mara Forasarig; Marcello Anti; Giovanni Neri; Maurizio Ponz de Leon; Alessandra Viel; et al. (Familial Cancer, 2001)

Characterization of MLH1 and MSH2 alternative splicing and its relevance to molecular testing of colorectal cancer susceptibility - Maurizio Genuardi; Alessandra Viel; Daniela Bonora; Eugenia Capozzi; Alfonso Bellacosa; Francesca Leonardi; Roberta Valle; Andrea Ventura; Monica Pedroni; Mauro Boiocchi; G. Neri (Human Genetics, 1998)